2019
DOI: 10.1021/acs.joc.9b00370
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Mediated Highly Diastereoselective Allylation of Aldehydes with Cyclic Allylic Halides

Abstract: Lead was found to efficiently mediate the allylation reactions of carbonyl compounds with cyclic allylic halides in the presence of stoichiometric amounts of lithium chloride and a catalytic amount of GaCl3 (20 mol %), leading to the desired homoallylic alcohols in modest to high yields with excellent diastereocontrol (>99:1 syn/anti) and good functional group tolerance. In contrast, the use of either 2-pyridinecarboxaldehyde as the carbonyl substrate or (E)-cinnamyl bromide as the allylating agent produced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The data are consistent with the literature. 37 R f = 0.16 (10% Et 2 O/n-hexane). 1-(4-Chlorophenyl)-pent-3-en-1-ol (5g) The title compound was prepared according to general procedure 1 from 4-chlorobenzaldehyde (45.2 mg, 0.321 mmol) and boronic ester 4g (72.5 mg, 0.398 mmol).…”
Section: (±)-Syn-(4-chlorophenyl)(cyclohex-2-en-1-yl)methanol (5f)mentioning
confidence: 99%
“…The data are consistent with the literature. 37 R f = 0.16 (10% Et 2 O/n-hexane). 1-(4-Chlorophenyl)-pent-3-en-1-ol (5g) The title compound was prepared according to general procedure 1 from 4-chlorobenzaldehyde (45.2 mg, 0.321 mmol) and boronic ester 4g (72.5 mg, 0.398 mmol).…”
Section: (±)-Syn-(4-chlorophenyl)(cyclohex-2-en-1-yl)methanol (5f)mentioning
confidence: 99%
“…As expected, preliminary studies showed that almost no desired product 3a was obtained when the reaction was performed in the absence of any catalyst (entry 1). When various metallic salts (20 mol %) were employed as the reaction catalyst (entries 2–15), such as InCl 3 , , GaCl 3 , PbCl 2 , , CrCl 3 , FeCl 3 , LiI, and CuI, which were demonstrated to be efficient catalysts for catalyzing some other organic reactions, the reactions proceeded with different performances to afford the corresponding β-hydroxyl ester 3a in poor yields, ranging between 2% and 39%. It was not until molecular iodine was introduced as a reaction catalyst that the yield of product 3a was remarkably improved to 90% (88% isolated yield; entry 16).…”
mentioning
confidence: 99%